How do Self with Classroom This study investigated in Math and Classroom Learning Environment (CLE) through quantitative approach Public Schools of Punjab were the population of the study. Using random sampling, 997 respondents (Boys = 489, Girls = 508) f (PJDOL, 2023)
This study investigated in Math and Classroom Learning Environment (CLE) through quantitative approach Public Schools of Punjab were the population of the study. Using random sampling, 997 respondents (Boys = 489, Girls = 508) from two districts(conveniently) were selected. The scale (Fraser, 2007). Self measured students’ self scale developed by the researchers was used.CLE and Retention in Math,similar perception regarding these variables with respect to their male counterparts. Findings revealed no significant relationship between CLE and SR of students for the whole sample as well; further, relationship betwe it was significant for females as compared to males.